Membangun Budaya Hak-Hak Asasi Manusia - Sardi, Martino (Jurnal Media Hukum, 2016)
The violations of Human Rights remain spread in all over the world until now. There are violations of Human Rights in all the countries in this universe. It is not possible to find a country, which free from this violation. It is very terrible, such as the professional killing and systematic murder. It will cause to grow the culture of dead. This culture does not respect on the human life. The professional killing and systematic murder are real social fact, which are not distinct and justly resolved. This criminal actions will grow more terrible, if the official organs of the government provoke and take apart in this matter, do not want to obstacle and stop them, although they are capable to do it. The culture of Human Rights can be built, if the culture of life has been respected, the people, especially the organ of the government takes care and respect to Human Rights and promote them as well as possible. So the human life will grows to the directions of the welfare for the people and more civilized. If the people develop the culture of Human Rights, the human civilizations will grow for respect them. We have task to develop the culture of Human Rights.